Rancang Bangun Suction Pump Portable dengan Tampilan Digital Menggunakan Arduino Uno R3 328p - Putri, Suci Imani; Firdaus, Ade; Suhartina, Rahmalisa; Mujakar, Samsul (Innovative: Journal Of Social Science Research, 2025)
This In the medical field, the use of appropriate medical devices is essential to support healthcare personnel in providing optimal services. This portable suction pump module with a digital display is designed to facilitate the adjustment and monitoring of suction pressure during medical procedures. The study began with a literature review, data collection, and needs analysis. Test results indicate that the suction pump can display real-time suction pressure according to user settings and meets the recommended suction pressure standards for various medical needs, including newborns, children, and adults. Testing with a Digital Pressure Meter demonstrated that the device has an average accuracy rate of 92.52% with an error value of 4.43%. These findings indicate that this portable suction pump is reliable for clinical use within international standard tolerance limits and supports usage in various medical conditions requiring high-precision suction power.